2011
DOI: 10.1039/c1ob05665d
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing dirhodium(ii) tetrakiscarboxylates as chiral NMR auxiliaries

Abstract: Thirteen enantiopure paddlewheel-shaped dirhodium(II) tetrakiscarboxylate complexes have been checked for their efficiency in the dirhodium method (differentiation of enantiomers by NMR spectroscopy); six of them are new. Their diastereomeric dispersion effects were studied and compared via so-called key numbers KN. Adducts of each complex were tested with five different test ligands representing all relevant donor properties from strong (phosphane) to very weak (ether). Only one of them, the dirhodium complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
0
33
1
Order By: Relevance
“…This fact was also previously observed through many other complexes from the same family [35,[49][50][51] including Rh 2 (S-PTAD) 4 which carry the bulkiest adamantyl groups at the ligands' α-positions [35]. This observation can be also applied to carbene ligands during asymmetric catalysis which contradicts with the major assumption of Fox mechanistic 4 in asymmetric cyclopropanations [47,48].…”
Section: Resultscontrasting
confidence: 43%
See 2 more Smart Citations
“…This fact was also previously observed through many other complexes from the same family [35,[49][50][51] including Rh 2 (S-PTAD) 4 which carry the bulkiest adamantyl groups at the ligands' α-positions [35]. This observation can be also applied to carbene ligands during asymmetric catalysis which contradicts with the major assumption of Fox mechanistic 4 in asymmetric cyclopropanations [47,48].…”
Section: Resultscontrasting
confidence: 43%
“…This is in contrast with the clockwise twist reported for [Rh 2 (S-PTTL) 4 . (EtOAc)] [47,48] and other related complexes [35,[49][50][51]. As a result, the daisy-chain type docking of the N-phthaloyl units around the cavity seen in [Rh 2 (S-PTTL) 4 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, 2D heteronuclear NOESY data reported by the groups of Charette [54] and Duddeck [99], independently, confirmed that Rh2(S-PTTL)4 and analogues have a mobile conformation in solution. This confirms the existence of other conformers with at least one N-phthalimido group is flipped downward.…”
Section: Global Catalyst Symmetrymentioning
confidence: 64%
“…In fact, carboxylate ligands contain conformationally mobile units [13,54,87,98,99] which might give the ability to the dirhodium(II) catalyst to adapt its conformation to the particular substrate undergoing the reaction. Then enantioselection mechanisms can mainly originate from the different preferred reaction channels as a function of the different steric interactions taking place between the approaching substrate and the formed dirhodium(II)-carbene complex.…”
Section: Discussionmentioning
confidence: 99%